The making of a blue revolution in Bangladesh: Enablers, impacts, and the path ahead for aquaculture - Rashid, Shahidur; Zhang, Xiaobo (International Food Policy Research Institute, 2019)
A rapid increase in aquaculture production in Bangladesh has lowered fish prices, increased protein consumption, and reduced poverty. The Making of a Blue Revolution in Bangladesh offers a valuable case study of how this transformation in the fish value chain has occurred and how it has improved the lives of both fish producers and fish consumers and considers the future potential of aquaculture in Bangladesh.